Peningkatan Kesiapan Diri Berdasarkan Ability, Skill & Demeanor dalam Menghadapi Revolusi Industri 4.0 Bagi Mahasiswa - Muhamad Suhardi; Zinnurain Zinnurain (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to identify the readiness of final semester students of the Faculty of Education and Psychology, Mandalika Education University for the 2020/2021 academic year in facing the world of work in the era of the industrial revolution 4.0. This research is a survey research with a qualitative descriptive approach. The population and sample are all final semester (8) students as many as 27 people who have carried out field practice for 5 months from March 2021 to July 2021. This research data consists of primary data obtained directly from respondents in the form of a questionnaire (measuring Affective and psychomotor) and tests in the form of statements (cognitive). Analysis of the data used is descriptive analysis with percentage calculations. The results showed that Ability was in the high category (79%), Skill was in the very high category (88%) and Demeanor (attitude) was in the high category (79%). The conclusion, based on the results of descriptive analysis and data classification, is the overall readiness of final semester students of the Faculty of Education and Psychology, Mandalika Education University to enter the world of work as a whole from the aspect of ability (Ability), skills (Skills) and attitudes (Demeanor) towards the field of production work. , service and managerial research results are in the very high category (85%). Keywords: self-readiness, ability, skill, demeanor, industrial revolution 4.0.